Diagnoses behind patients with hard-to-classify tremor and normal DaT-SPECT: a clinical follow up study - Menéndez-González, Manuel; Tavares, Francisco; Zeidan, Nahla; Salas-Pacheco, José M.; Arias-Carrión, Oscar (Frontiers in Aging Neuroscience, 2014)
The [123I]ioflupane - a dopamine transporter radioligand - SPECT (DaT-SPECT) has proven to be useful in the differential diagnosis of tremor. Here, we investigate the diagnoses behind patients with hard-to-classify tremor and normal DaT-SPECT. Therefore, 30 patients with tremor and normal DaT-SPECT were followed up for 2 years. In 18 cases we were able to make a diagnosis. The residual 12 patients underwent a second DaT-SPECT, were then followed for additional 12 months and thereafter the diagnosis was reconsidered again. The final diagnoses included cases of essential tremor, dystonic tremor, multisystem atrophy, vascular parkinsonism, progressive supranuclear palsy, corticobasal degeneration, fragile X–associated tremor ataxia syndrome, psychogenic parkinsonism, iatrogenic parkinsonism and Parkinson’s disease. However, for 6 patients the diagnosis remained uncertain. Larger series are needed to better establish the relative frequency of the different conditions behind these cases.